MOX catalyst modified monocrystalline TA3N5 nanoparticles, catalyst, catalytic water splitting method, and method for producing same

Through the improved tantalum nitride photocatalyst design, the problem of low quantum efficiency of photocatalysts in the visible light region in the prior art is solved, and more efficient water decomposition performance is achieved.

JP2025507389APending Publication Date: 2025-03-18GLOBAL ADVANCED METALS USA INC +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024547839
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-15
Filing Date
2023-02-14
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the existing photocatalytic water decomposition technology, the quantum efficiency of the photocatalyst is low in the visible light region, limiting its application in large-scale clean fuel production.

Method used

The improved tantalum nitride (Ta3N5) photocatalyst is used to improve its photocatalytic activity under visible light through the design of single-crystal nanoparticles and alloy structure.

Benefits of technology

The quantum efficiency and gas generation rate of the tantalum nitride photocatalyst are significantly improved, and its photocatalytic properties in water decomposition are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507389000001_ABST
    Figure 2025507389000001_ABST
Patent Text Reader

Abstract

Tantalum nitride, specifically novel Ta3N5 nanoparticles, such as single crystal Ta3N5 nanoparticles, are disclosed. Nanoparticles for use with cocatalysts are further disclosed. The present invention also provides a method for the preparation of a tantalum nitride nanoparticle having a cocatalyst function. x The present invention relates to Ta3N5 nanoparticles modified with metal oxides such as promoters, x represents an oxide that is a part of cobalt oxide. A catalyst for oxidizing water to produce O2 is disclosed. The nanoparticles can be further modified to include a water reduction catalyst. A water splitting catalyst is further disclosed. Methods for making the nanoparticles and catalysts are also disclosed. Methods for splitting water utilizing the catalyst are also described.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] This application claims the benefit under 35 USC § 119(e) of earlier U.S. Provisional Patent Application No. 63 / 310,237, filed February 15, 2022, the entire contents of which are incorporated herein by reference.

[0002] The use of solar energy in the presence of photocatalysts to split water to produce hydrogen and oxygen has been investigated as a potential means of large-scale clean fuel production. Hydrogen fuel production has attracted increasing attention due to concerns about global warming. Methods such as photocatalytic water splitting have been investigated to produce hydrogen, a clean fuel. Water splitting is particularly promising because it utilizes water, an inexpensive renewable resource. Photocatalytic water splitting has its simplicity in that it uses a catalyst and sunlight to produce hydrogen from water.

[0003] In contrast to the two-step system of photovoltaics followed by water electrolysis, the photocatalytic water splitting process is carried out by direct contact of the photocatalyst with water. The photocatalyst is in a homogeneous environment with respect to the water (photocatalyst suspended in the water) or in a heterogeneous phase with respect to the water (photocatalyst bound to a surface in contact with the water). Examples of heterogeneous photocatalytic processes include those described in US Pat. No. 5,399,433 and US Pat. No. 5,499,433, the methods of which can be utilized with the catalysts of the present invention and are incorporated by reference in their entirety herein. Photocatalytic water splitting, whether homogeneous or heterogeneous, is more efficient than the two-step process of water electrolysis.

[0004] The main indicator of the effectiveness of a photocatalyst is the quantum yield (QY), where QY(%) = (photochemical reaction rate) / (photon absorption rate) × 100%. This quantity is a reliable measure of how effective a photocatalyst is. Overall, the best photocatalysts have higher quantum yields and faster gas generation rates. Nearly all reported photocatalytic water splitting systems have been reported to have low QY in the visible light region (e.g., rarely exceeding 3% at 420 nm), severely hindering their potential practical applications.

[0005] To address the growing global problems of energy shortages and environmental destruction, artificial photosynthesis (water splitting and CO 2 Reduction of CO2 emissions (reduction of CO2 emissions) is a promising method for converting solar energy into high-value chemical energy (Non-Patent Document 1; and Non-Patent Document 2).

[0006] Photocatalytic water splitting typically involves two separate reaction pathways leading to the production of hydrogen and oxygen: 2 O=>2H 2 +O 2

[0007] The photocatalyst can enhance the hydrogen pathway to catalyze the corresponding reduction reaction, and / or the photocatalyst can enhance the oxygen pathway to catalyze the corresponding oxidation reaction. It is desirable to utilize a photocatalyst that can simultaneously promote both the hydrogen pathway and the oxygen pathway and do so efficiently.

[0008] The oxidation of water (involving the transfer of four electrons and the formation of an O=O bond) converts water to H 2 and O 2 Not only does it decompose into CO 2 This is a key step in the reduction of acetylene to carbon-containing chemicals (Non-Patent Document 3; Non-Patent Document 4; Non-Patent Document 5).

[0009] Since visible light (wavelengths 400nm to 800nm) occupies a large portion of the solar spectrum, it may be important to develop a semiconductor photocatalyst that can react under a wide range of visible light irradiation in order to achieve the expected solar energy conversion efficiency. 3 N 5 Ta has been considered for use in solar water splitting due to its simple chemical composition, narrow band gap energy (2.1 eV), and suitable band position spanning the redox potential of water. 3 N 5 is the half-reaction H 2 Or O 2(Non-Patent Document 6, Non-Patent Document 7, Non-Patent Document 8, and Non-Patent Document 9), which has been reported to be capable of water splitting by a single excitation step (Non-Patent Document 10).

[0010] Due to its hydroxylation ability, Z-scheme water splitting and O 2 Ta for development 3 N 5 Significant improvements have been achieved in photoelectrochemical water splitting using (Non-Patent Document 11, Non-Patent Document 12, Non-Patent Document 13, and Non-Patent Document 14).

[0011] High quality Ta 3 N 5 Photocatalysis is highly desirable to efficiently enhance the separation of photoexcited charges and the transfer of electrons and holes to surface sites for photocatalytic reactions. 3 N 5 The photocatalyst is usually a powder of Ta 2 O 5 The precursor was reacted with NH 3 However, it is composed of agglomerated polycrystalline particles with crystal defects and impurity energy levels that adversely affect the oxidation activity of the photocatalyst. 2 To promote development, 2 O 5 Ta from precursor 3 N 5 It is necessary to modify it with alkali metals or magnesium oxide to adjust the morphology and surface properties of Ta. 3 N 5 KTaO with a lattice spacing close to that of 3 When potassium, which is easily evaporated at high temperatures, was used as the unique starting metal oxide, Ta with minimized defect states was obtained. 3 N 5 Single nanorod crystals were synthesized by NH 3 Nitridation process of KTaO 3 Rapid growth on the cube and global water splitting by visible light-driven single-step excitation of H 2 and O 2 This shows that Ta 3 N 5Precursors for the synthesis of Ta for efficient solar-to-chemical energy conversion 3 N 5 We show that Ta particles have important functions in manipulating the morphology, crystallinity, nanostructure, and defect state of Ta. 3 The oxidation reaction of Ta 2 O 5 The well-crystallized Ta 3 N 5 It can be considered as a promising material for the growth of photocatalysts, which greatly shortens the nitridation process. In the same short-term nitridation process, Ta metal powder is transformed into single-phase Ta 3 N 5 whereas Ta 2 O 5 It has been reported that no NH is produced. 3 Doped Ta nanoparticles synthesized from Ta metal nanopowder by nitridation process 3 N 5 The single crystals showed dramatically enhanced photocatalytic water reduction activity (H 2 They have demonstrated the high availability of nanosized Ta metal precursors (Non-Patent Document 15, Non-Patent Document 16, Non-Patent Document 17, and Non-Patent Document 18).

[0012] Ta 3 N 5 Ta is considered a promising photocatalyst for solar water splitting due to its excellent visible light absorption and simple crystalline structure. However, conventional Ta 3 N 5 Photocatalysts generally have agglomerated polycrystalline particles with defect states and grain boundaries, limiting significant enhancement of photocatalytic water oxidation activity. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] US10,744,495 [Patent Document 2] US2014 / 0174905

Non-licensed literature

[0014] [Non-licensed document 1] Chen, [Non-licensed document 2] Wang, Z.; Li, C.; Domen, K.Recentdevelopments in heterogeneous photocatalysts for solar-driven overallwatersplitting. Chem. Soc. Rev. 2019, 48, 2109-2125 [Non-licensed document 3] Wang, Y.; Suzuki, H.; Xie, J.; Tomita,O.;Martin, DJ; Higashi, M.; Kong, D.; Abe, R.;

Non-licensed Document 4

Non-licensed Document 5

Wood 6

Waterfall 7

Fashion 8

Non - Patent Document 16

Non - Patent Document 17

Non - Patent Document 18

[0015] Thus, improved Ta nanoparticles that are single crystalline nanoparticles and / or provide improved catalytic properties, such as, but not limited to, improved photocatalytic water oxidation activity, are provided. 3 N 5 There is a need to provide nanoparticles and a catalyst.

[0016] Thus, there is a need to provide improved nanoparticles, particularly improved tantalum nitride, for use in industry, for example as catalysts, in water splitting processes and / or other applications. [Means for solving the problem]

[0017] Thus, a feature of the present invention is the production of novel tantalum nitrides, specifically novel Ta 3 N 5 Nanoparticles, e.g. single crystal Ta 3 N 5 The present invention provides nanoparticles.

[0018] A further feature is that the Ta 3 N 5 The present invention provides nanoparticles.

[0019] Another feature of the present invention is the oxidation of water to O 2 The object of the present invention is to provide a catalyst for producing

[0020] Another feature of the present invention is the oxidation of water to O 2 Catalyst for the production of H by reduction of water 2 The present invention provides a single catalyst, such as a catalyst for producing

[0021] Another feature of the present invention is to oxidize water to O by a catalytic mixture of a water oxidation catalyst and a water reduction catalyst. 2 and a catalyst for the reduction of water to H 2 and providing a catalyst for producing the same.

[0022] Another feature of the present invention is to provide a water splitting catalyst.

[0023] Another feature of the present invention is to provide a method for splitting water using nanoparticles, such as in the form of a catalyst.

[0024] Another feature of the present invention is to provide methods for producing the novel tantalum nitrides and catalysts.

[0025] Additional features and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by the practice of the invention. The objectives and other advantages of the invention will be realized and attained by means of the elements and combinations particularly pointed out in the description and appended claims.

[0026] To achieve these and other advantages, and in accordance with the purposes of the invention as embodied and broadly described herein, the present invention relates in part to a tantalum nitride, particularly Ta 3 N5 and, in particular, the use of Ta as a catalyst, including, but not limited to, 3 N 5 Contains or Ta 3 N 5 Relating to products made from

[0027] The present invention also provides a method for producing a CoO x Ta modified with metal oxides as promoters 3 N 5 The present invention relates to nanoparticles, x represents an oxide that is a part of cobalt oxide.

[0028] The present invention further comprises a CoO x Single crystal Ta modified with metal oxides as promoters 3 N 5 The present invention relates to nanoparticles, x represents an oxide that is part of the cobalt oxide family.

[0029] Furthermore, the present invention provides a CoO x Modified with a metal catalyst such as a cocatalyst (e.g., single crystal) Ta 3 N 5 Nanoparticles or Ta 3 N 5 The present invention relates to a nanoparticle photocatalyst, x represents an oxide that is part of the cobalt oxide family.

[0030] The present invention also provides a CoO x Single crystal Ta modified with metal oxide promoters such as cocatalysts 3 N 5 The present invention relates to a catalyst comprising nanoparticles, where platinum and / or other catalytic metals are distributed on the surface of single crystal nanoparticles.

[0031] Further, the present invention provides: (1) CoO x Modified with a metal catalyst such as a cocatalyst (e.g., single crystal) Ta 3 N 5 Nanoparticles or Ta 3 N 5The present invention relates to a catalyst which is a nanoparticle, x are part of cobalt oxides, and (2) oxides modified or doped with one or two metals such as Zr and / or Mg (e.g., Ta 3 N 5 : Mg+Zr, Ta 3 N 5 :Mg, Ta 3 N 5 :Zr, or any combination thereof).

[0032] The promoter can be impregnated, deposited, distributed, or dispersed on or used in conjunction with the single crystal nanoparticles.

[0033] The present invention further relates to a mixture of catalysts, where a first catalyst is a water oxidation catalyst and a second catalyst is a water reduction catalyst (or a catalyst that reduces water). For example, the mixture may include a first catalyst, CoO x Modified with a metal catalyst such as a cocatalyst (e.g., single crystal) Ta 3 N 5 Nanoparticles or Ta 3 N 5 The nanoparticles may be x represents an oxide that is a part of cobalt oxide, and the second catalyst is modified or doped with one or two metals such as Zr and / or Mg (e.g., Ta 3 N 5 : Mg+Zr, Ta 3 N 5 :Mg, Ta 3 N 5 :Zr, or any combination of these).

[0034] The present invention further relates to a method for producing a monocrystalline nanoparticle of the present invention, comprising the steps of: x The present invention relates to a catalyst comprising a co-catalyst, which may be platinum metal (Pt) uniformly distributed or dispersed on the single crystal nanoparticles, or mixed with the nanoparticles, or used in combination with the nanoparticles.

[0035] The present invention further relates to a metal cocatalyst (e.g., CoO x The present invention relates to a catalyst that uses a catalyst comprising the single crystal nanoparticles of the present invention together with a co-catalyst in combination with a water reduction catalyst. For example, the water reduction catalyst for the reduction reaction can utilize single crystal nanoparticles that are tantalum nitride, optionally doped with at least one metal. In the reduction reaction, Ta 3 N 5 : Mg+Zr, Ta 3 N 5 :Mg, Ta 3 N 5 In the reduction reaction, single crystal nanoparticles of Ta, Zr, or any combination of these can be used. 3 N 5 : Mg+Zr, Ta 3 N 5 :Mg, Ta 3 N 5 :Zr, or any combination thereof, can be utilized along with at least one co-catalyst (eg, Pt).

[0036] Furthermore, the present invention relates to a method of water splitting, which includes utilizing a catalyst (e.g., photocatalyst) of the present invention in contact with water or other fluid. The method can further include the use of an additional catalyst (e.g., photocatalyst), where one catalyst is a water oxidation catalyst described herein and the additional catalyst is a water reduction catalyst described in U.S. Provisional Patent Application No. 63 / 184816, filed May 6, 2021, or WO2022 / 235721 (herein incorporated by reference). The two catalysts can be used as a mixture on the same single crystal nanoparticle of the present invention, or can be used together as a mixture of nanoparticles and introduced or used in any order.

[0037] The present invention further relates to a method for water splitting, comprising using a catalyst (e.g., a photocatalyst) of the present invention in contact with water or other fluids, the single / same catalyst having two functions: a water oxidation catalyst as described herein and a water reduction catalyst as described in U.S. Provisional Patent Application No. 63 / 184816, filed May 6, 2021, or WO2022 / 235721, which are incorporated herein by reference.

[0038] The present invention also relates to a method for producing the nanoparticles or catalyst of the present invention, comprising a nitridation process comprising subjecting spherical tantalum powder or tantalum agglomerates with salt agglomerates, or a flame synthesized tantalum, which may optionally be encapsulated with salt, to a nitridation process, the nitridation process comprising subjecting spherical tantalum powder or tantalum agglomerates with salt agglomerates, or a flame synthesized tantalum, which may optionally be encapsulated with salt, to a nitridation process comprising subjecting spherical tantalum powder or tantalum agglomerates with salt agglomerates ... 3 The nitridation is carried out under a flow at a temperature of 700K or more for 10 minutes to 4 hours or more to form tantalum nitride, and then the tantalum nitride is treated with CoO x The present invention includes impregnating a catalyst with a metal oxide promoter such as

[0039] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are intended to provide further explanation of the invention as claimed. [Brief description of the drawings]

[0040] [Figure 1] FIG. 1 shows XRD patterns of (a) Ta nanoparticle precursor (w / oNaCl / Ta) used in the examples of this application, and products produced by nitridation at (b) 773 K, (c) 923 K, (d) 1023 K, (e) 1073 K, and (f) 1123 K for 10 minutes, and (h) Ta3N5 obtained from Ta nanopowder (w / oNaCl / Ta) nitrided at 1173 K for 4 hours. [Figure 2A]Figure 2A shows the XRD patterns obtained from Ta3N5 nanoparticles produced using Ta nanopowder (w / oNaCl / Ta) nitrided at different temperatures for 4 h. [Figure 2B] FIG. 2B shows the UV-Vis DRS data obtained from Ta3N5 nanoparticles produced using Ta nanopowder (w / oNaCl / Ta) nitrided at different temperatures for 4 h. [Figure 2C] Fig. 2C is a bar graph showing the relationship between the nitridation temperature and the O2 generation rate of the catalyst of the present invention. Photocatalytic O2 generation on these Ta3N5 nanoparticles. Conditions: catalyst, 0.15 g; CoOx loading, 0.5 wt%; 0.2MAgNO3 aqueous solution, 150 mL; La2O3 buffer, 0.15 g; light source, 300 W xenon lamp (λ ≧ 420 nm). [Figure 2D] Figure 2D is an SEM image of Ta3N5 nanoparticles prepared by nitriding Ta nanopowder (w / oNaCl / Ta) at 1173 K for 4 h. [Figure 2E] Figure 2E shows HRTEM and SAED images of Ta3N5 nanoparticles prepared by nitriding Ta nanopowder (w / oNaCl / Ta) at 1173 K for 4 h. [Figure 3A] Figure 3A shows the XRD patterns and Figure 3B shows the bar graphs showing the photocatalytic O2 evolution activity of Ta3N5 nanoparticles prepared from NaCl mixed Ta nanopowder (NaCl / Ta) nitrided at different temperatures for 16 h. Conditions: catalyst, 0.15 g; CoOx loading, 0.5 wt%; 0.2M AgNO3 aqueous solution, 150 mL; La2O3 buffer, 0.15 g; light source, 300 W xenon lamp (λ ≧420 nm). [Figure 3B] Figure 3A shows the XRD patterns and Figure 3B shows the bar graphs showing the photocatalytic O2 evolution activity of Ta3N5 nanoparticles prepared from NaCl mixed Ta nanopowder (NaCl / Ta) nitrided at different temperatures for 16 h. Conditions: catalyst, 0.15 g; CoOx loading, 0.5 wt%; 0.2 M AgNO3 aqueous solution, 150 mL; La2O3 buffer, 0.15 g; light source, 300 W xenon lamp (λ ≧420 nm). [Figure 3C]FIG. 3C is an SEM image of these nanoparticles of FIG. 3A. [Figure 3D] Figure 3D is an HRTEM image of Ta3N5 nanoparticles prepared from NaCl mixed Ta nanopowder (NaCl / Ta) nitrided at 1073 K for 16 h. [Figure 4] Figure 4 shows the wavelength vs. AQY plot: apparent quantum yield of Ta3N5 nanoparticles prepared from NaCl mixed Ta nanopowder (NaCl / Ta) nitrided for 16 h at 1073 K during photocatalytic O2 evolution as a function of incident light wavelength. Conditions: catalyst, 0.15 g; CoOx loading, 0.5 wt%; 0.2 M AgNO3 aqueous solution, 150 mL; La2O3 buffer, 0.15 g; light source, 300 W xenon lamp with various bandpass filters. [Diagram 5] FIG. 5 is a SEM image of Ta metal nanopowder (w / oNaCl / Ta) that was nitrided to form Ta3N5 in an embodiment of the present invention. [Figure 6] Figure 6 shows the time course of photocatalytic O2 evolution over Ta3N5 nanoparticles produced using Ta nanopowder (w / oNaCl / Ta) nitrided for 4 h at different temperatures. Conditions: catalyst, 0.15 g; CoOx loading, 0.5 wt%; 0.2 M AgNO3 aqueous solution, 150 mL; La2O3 buffer, 0.15 g; light source, 300 W xenon lamp (λ ≧420 nm). [Figure 7] Figure 7A is an XRD pattern, and Figure 7B is a graph showing the relationship between nitridation time and O2 generation rate, specifically, the photocatalytic O2 generation activity of Ta3N5 nanoparticles obtained by nitriding Ta nanopowder (w / oNaCl / Ta) at different time intervals at 1173 K. Conditions: photocatalyst, 0.15 g; CoOx loading, 0.5 wt%; 0.2 M AgNO3 aqueous solution, 150 mL; La2O3 buffer, 0.15 g; light source, 300 W xenon lamp (λ ≧420 nm). [Figure 8]Figure 8 is a graph showing the relationship between the amount of CoOx loaded and the O2 generation rate. Figure 8 specifically shows the effect of loading of CoOx cocatalyst on photocatalytic performance using Ta3N5 nanoparticles synthesized from Ta nanopowder (w / oNaCl / Ta) at 1173K for 4 hours. Conditions: Photocatalyst, 0.15g; 0.2M AgNO3 aqueous solution, 150mL; La2O3 buffer, 0.15g; Light source, 300W xenon lamp (λ ≧420nm). [Figure 9] FIG. 9 is a SEM image of the NaCl mixed Ta metal nanopowder (NaCl / Ta) used in the examples of the present invention. [Figure 10A] 10A is a bar graph showing the relationship between the nitridation temperature and the O2 evolution rate of the catalyst of the present invention, i.e., Ta3N5 nanoparticles obtained from NaCl-mixed Ta nanopowder (NaCl / Ta) nitrided at 1073 K for different time ranges: Photocatalytic O2 evolution activity of Ta3N5 nanoparticles obtained by nitriding NaCl-mixed Ta nanopowder (NaCl / Ta) at 1073 K for different time ranges. Conditions: photocatalyst, 0.15 g; CoOx loading, 0.5 wt%; 0.2 M AgNO3 aqueous solution, 150 mL; La2O3 buffer, 0.15 g; light source, 300 W xenon lamp (λ ≧420 nm). [Figure 10B] FIG. 10B is an XRD pattern of the catalyst tested in FIG. 10A. [Figure 10C] FIG. 10C is a SEM image of Ta3N5 nanoparticles obtained from NaCl mixed Ta nanopowder (NaCl / Ta) nitrided at 1073 K for different time ranges tested in FIG. 10A. [Figure 11A] 11A-C are standard XRD patterns of TaN0.1 (FIG. 11A), TaN (FIG. 11B), and Ta3N5 (FIG. 11C). [Figure 11B] 11A-C are standard XRD patterns of TaN0.1 (FIG. 11A), TaN (FIG. 11B), and Ta3N5 (FIG. 11C). [Figure 11C] 11A-C are standard XRD patterns of TaN0.1 (FIG. 11A), TaN (FIG. 11B), and Ta3N5 (FIG. 11C). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] The present invention is x Ta modified with metal oxides as promoters 3 N 5 The present invention relates to tantalum nitride nanoparticles, such as nanoparticles. The nanoparticles can be catalysts alone or can be part of a catalyst. The catalysts can be used in a variety of processes, such as methods for splitting water. The present invention further relates to methods for making tantalum nitride nanoparticles and catalysts. Preferably, the nanoparticles are CoO x Ta modified with metal oxides as promoters 3 N 5 Tantalum nitride nanoparticles, such as nanoparticles, are used as water oxidation catalysts.

[0042] Tantalum nitride nanoparticles can be further modified to also function as water reduction catalysts, as described herein. Tantalum nitride nanoparticles functioning as water oxidation catalysts can be used in combination with tantalum nitride nanoparticles functioning as water reduction catalysts. Dual catalysts can be used on the same tantalum nitride nanoparticles or as a mixture of tantalum nitride nanoparticles (a mixture of tantalum nitride nanoparticles as a water oxidation catalyst and a mixture of tantalum nitride nanoparticles as a water reduction catalyst, combined as a mixture of the two types of nanoparticles).

[0043] A specific example of tantalum nitride is Ta 3 N 5 There is.

[0044] Other examples of tantalum nitride include Ta 4 N 5 , Ta 5 N 6 , Ta 2 N, TaN, etc., but are not limited to these. In general, TaN x (x is in the range of 0.1 to 3).

[0045] Tantalum nitride may be an n-type semiconductor, preferably with a narrow band gap and / or suitable energy positions of the conduction and valence bands that span the redox potential of water.

[0046] The Ta 3 N 5 The nanoparticles may be single crystal nanoparticles.

[0047] The Ta 3 N 5 The nanoparticles are single-crystalline nanoparticles modified with at least one cocatalyst, e.g., nanoparticles having the general formula MO x (In the formula, M represents a metal, O x The nanoparticles may be monocrystalline nanoparticles modified with a metal oxide, such as CoO x , MnO x , FeO x , NiO x , IrO x , and RuO x In this specification, CoO x Although certain embodiments of the present invention may be described in terms of metal oxides, for purposes of the present invention, CoO x It should be understood that the details and discussion relating to apply to other metal oxides as well.

[0048] Ta 3 N 5 The nanoparticles are single-crystal Ta 3 N 5 The nanoparticles may be monodisperse, such as monodisperse nanoparticles, where monodisperse means having particles of approximately the same size. A monodisperse distribution may be a distribution in which the particle sizes of a population of nanoparticles are within 20%, within 10%, within 5%, or within 1% of each other. Particle size may be measured by a laser diffraction particle size analyzer such as the Horiba Scientific Partica LA-960V2, or a dynamic light scattering particle size analyzer such as the Horiba Scientific nanoPartica SZ-100V2 series.

[0049] The nanoparticles of the present invention described above or herein may be monodisperse nanoparticles, with the crystalline phase being a single crystalline phase. The crystalline particles of the present invention may be substantially free or detectably free of minor segregation phases such as Ta, Ca or similar minor phases.

[0050] As a more specific example, and with reference to a preferred embodiment, the nanoparticles may be CoO x Single crystal Ta modified with promoter 3 N 5 Nanoparticles, where O x represents an oxide that is a part of cobalt oxide.

[0051] Chief of Staff x The metal oxide promoter, such as the cocatalyst, is present in an amount sufficient to function as a water oxidation catalyst, e.g., single crystal Ta 3 N 5 Ta in an amount of at least 0.01 wt. % based on the total weight of the nanoparticles 3 N 5 The amount of metal oxide-modified Ta nanoparticles is 3 N 5 Nanoparticle photocatalysts (e.g., CoO x Modified Ta 3 N 5 Based on the total weight of the nanoparticle photocatalyst, it may be at least 0.05 wt.%, or at least 0.1 wt.%, or at least 0.25 wt.%, or at least 0.5 wt.% or more, for example, 0.01 wt.% to 1 wt.% or more, or 0.05 wt.% to 1 wt.%.

[0052] Chief of Staff x The promoter is CoO, Co 2 O, Co 2 O 3 , and / or Co. 3 O 4 , or any combination or mixture thereof.

[0053] Single crystal nanoparticles (e.g., Ta modified with at least one cocatalyst) 3 N5 Nanoparticles, e.g., at least one metal oxide (e.g., CoO x Ta modified with cocatalyst 3 N 5 The nanoparticles) can have an apparent quantum yield of at least 5% at 420 nm, at least 7.5% at 420 nm, at least 9%, at least 10%, for example, 5% to 10% or more at 420 nm.

[0054] The present invention further provides single crystal nanoparticles (e.g., Ta modified with at least one cocatalyst). 3 N 5 Nanoparticles, e.g., at least one metal oxide (e.g., CoO x Ta modified with cocatalyst 3 N 5 The present invention relates to catalysts such as photocatalysts that are nanoparticles or that include single crystal nanoparticles.

[0055] The catalyst is NH 3 They may also be single crystalline nanoparticles formed by a nitridation process such as nitridation.

[0056] The catalyst, such as the photocatalyst of the present invention, has a fluorine content of more than 200 μmol / h, more than 400 μmol / h, or more than 600 μmol / h, or more than 700 μmol / h, for example, 200 μmol / h to 800 μmol / h. 2 It may have properties that provide generation.

[0057] The catalyst (e.g., photocatalyst) of the present invention is photocatalyst O 2 It may have properties that provide an apparent quantum yield (AQY) of the evolution reaction (OER) of greater than 0.1%, for example, from 0.1% to 9.4% (e.g., within 20%, within 10%, or within 5% of the 9.4% value).

[0058] When the catalyst used also includes a water reduction catalyst as described herein (either as part of the same catalyst or used in combination with a water oxidation catalyst), the catalyst, such as a photocatalyst, of the present invention can have properties that provide a sunlight-to-hydrogen (STH) energy conversion efficiency of greater than 0.015%, e.g., 0.015% to 0.1% or greater.

[0059] When the catalyst used also includes a water reduction catalyst as described herein (used as part of the same catalyst or in combination with a water oxidation catalyst), the catalyst, such as a photocatalyst of the present invention, can provide a H2O content of greater than 5 μmol / h, greater than 7 μmol / h, greater than 9 μmol / h, greater than 10 μmol / h, or greater than 12 μmol / h, for example, from 5 μmol / h to 13 μmol / h. 2 It may have properties that provide generation.

[0060] When the catalyst used also includes a water reduction catalyst as described herein (either as part of the same catalyst or in combination with a water oxidation catalyst), the catalyst, such as the photocatalyst of the present invention, may be used in combination with the photocatalyst H. 2 The compound may have properties that provide an apparent quantum yield (AQY) of the HER that is greater than 0.15%, for example, from 0.15% to 0.54% (e.g., within 20%, within 10%, or within 5% of the 0.54% value).

[0061] When the catalyst used also includes a water reduction catalyst as described herein (used as part of the same catalyst or in combination with a water oxidation catalyst), the catalyst is capable of absorbing more than 200 μmol / h of O 2 Generation, for example, of 200 μmol / h to 800 μmol / h O 2 and providing more than 5 μmol / h H 2 Production, e.g., 5 μmol / h to 13 μmol / h H 2 and photocatalyst O 2 The apparent quantum yield (AQY) of the evolution reaction (OER) is greater than 0.1%, e.g., 0.1% to 9.4%, and the photocatalytic H 2The catalyst may have both properties, such as an apparent quantum yield (AQY) of the evolution reaction (HER) of greater than 0.15%, e.g., between 0.15% and 0.54%, and the catalyst may further have the STH properties described herein.

[0062] The present invention further provides single crystal nanoparticles (Ta modified with at least one cocatalyst). 3 N 5 Nanoparticles, e.g. CoO x Ta modified with metal oxides as promoters 3 N 5 The present invention relates to a catalyst comprising platinum and / or other catalytic metals further modified or dispersed on the surface of single crystal nanoparticles.

[0063] The present invention further relates to a method for preparing a monocrystalline nanoparticle of the present invention using a metal oxide cocatalyst (e.g., CoO x The present invention relates to the use of a catalyst comprising a co-catalyst (co-catalyst) as a water oxidation catalyst in combination with a water reduction catalyst (described herein) in photocatalytic water splitting.

[0064] The catalyst, such as the photocatalyst, may be a crystalline nanoparticle as described herein (Ta modified with at least one cocatalyst). 3 N 5 Nanoparticles, e.g. CoO x Ta modified with metal oxides as promoters 3 N 5 The catalyst for at least water oxidation may comprise, consist essentially of, consist of, comprise, or be one of the following:

[0065] For example, Ta 3 N 5 The nanoparticle photocatalyst is a sacrificial AgNO 3 Solution (sacrificial AgNO 3 solution) to O 2 It can have high photocatalytic performance for generating

[0066] The catalyst of the present invention is pure Ta3 N 5 (e.g., under visible light irradiation) can have a higher photocatalytic water oxidation activity than that of the non-photocatalytic catalyst, which can be 5% or more higher, 10% or more higher, or 15% or more higher.

[0067] For example, the nanoparticles or catalysts of the present invention (Ta modified with at least one cocatalyst) 3 N 5 Nanoparticles, e.g. CoO x Ta modified with metal oxides as promoters 3 N 5 nanoparticles) at least 200 μmol / h, at least 300 μmol / h, or at least 450 μmol / h O 2 O generation rate, e.g., 200 μmol / h to 800 μmol / h, 200 μmol / h to 700 μmol / h, 200 μmol / h to 600 μmol / h, or 200 μmol / h to 500 μmol / h 2 It can have a rate of occurrence.

[0068] When multiple tantalum nitrides are present within a population of nanoparticles, the distribution between the two or more different tantalum nitrides can be uniform or non-uniform. 3 N 5 can be present at the highest weight percent based on the total weight of all tantalum nitrides present. Optionally, only one type of tantalum nitride is present in the population of nanoparticles.

[0069] The single crystal nanoparticles of the present invention are anosovite-type tantalum nitride, e.g., anosovite-type Ta 3 N 5 A single-phase X-ray diffraction (XRD) pattern related to

[0070] The single crystal nanoparticles of the present invention can have a variety of shapes, for example, the nanoparticles can have shapes that are considered to be nanorod-like particles and / or spherical particles, such as monodisperse nanorod particles or monodisperse spherical particles.

[0071] When the nanoparticles are nanorod particles, the nanorod particles can have a length. The length can be 50nm to 500nm or more, for example, 50nm to 450nm, 50nm to 400nm, 50nm to 350nm, 50nm to 300nm, 50nm to 250nm, 50nm to 200nm, 50nm to 150nm, 75nm to 500nm, 100nm to 500nm, 125nm to 500nm, 150nm to 500nm, 175nm to 500nm, 200nm to 500nm, 225nm to 500nm, 250nm to 500nm, 275nm to 500nm, 300nm to 500nm, etc. The length is considered to be an average length. Length (and width) measurements can be performed using images taken with a scanning electron microscope, analysing a minimum of three images per sample and measuring a minimum of 10 particles per image, in total measuring the length and width of a minimum of 30 particles and obtaining an average length and average width.

[0072] When the nanoparticles are nanorods, the aspect ratio (length / width) of the nanorods is at least 1.2 (e.g., at least 1.3, or at least 1.4, or at least 1.5, or at least 1.7, or at least 2, or at least 2.5, or at least 3, or at least 4, e.g., 1.2 to 4 or more, or 1.3 to 4, or 1.4 to 4, etc.).

[0073] When the nanoparticles are spherical, the average particle size (e.g., diameter) of the spherical nanoparticles is from 20 nm to 500 nm or more, for example, 50 nm to 500 nm or more, for example, 50 nm to 450 nm, 50 nm to 400 nm, 50 nm to 350 nm, 50 nm to 300 nm, 50 nm to 250 nm, 50 nm to 200 nm, 50 nm to 150 nm, 75 nm to 500 nm, 100 nm to 500 nm, 125 nm to 500 nm, 150 nm to 500 nm, 175 nm to 500 nm, 200 nm to 500 nm, 225 nm to 500 nm, 250 nm to 500 nm, 275 nm to 500 nm, 300 nm to 500 nm, etc. The measurement / method can be performed using a laser diffraction type particle size distribution analyzer or a dynamic light scattering type particle size distribution analyzer.

[0074] Optionally, tantalum nitride (e.g., Ta 3 N 5 ) is Ta 3 N 5 The atomic ratio of surface Ta in the form of (N-Ta-N) can be greater than 90 at% (e.g., 91 at% or more, 92 at% or more, 95 at% or more, 91 at% to 99 at%, 91 at% to 98 at%, 92 at% to 98 at%, 93 at% to 98 at%, or 94 at% to 98 at%).

[0075] Optionally, tantalum nitride (e.g., Ta 3 N 5 ) is Ta 3+ In the form of the Ta, the atomic ratio of the surface Ta can be less than 1 at% (for example, 0.9 at% or less, 0.8 at% or less, 0.5 at% or less, for example, 0.001 at% to 0.9 at%, or 0.01 at% to 0.5 at%). 3+ The atomic ratio of surface Ta in the form of is not detectable or is less than 0.001 at %.

[0076] Optionally, tantalum nitride (e.g., Ta 3 N 5 ) is TaO x N y The atomic ratio of surface Ta may be 2 at% or more in the form (O-Ta-N), the atomic ratio being from 2 at% to 5 at%, where x and y are such that N / O is preferably greater than 2, or greater than 3, or greater than 4, or greater than 4.5, or greater than 4.8.

[0077] The crystalline particles of the present invention may have a charge imbalance resulting in an oxygen to anion (O / N+O) molar ratio of 3.0% or more, or 4.0% or more, for example, 3.0% to about 18%, or 5% to about 18%, or about 7% to about 18%, or about 10% to about 18%, or about 12% to about 18%, or 15% or more.

[0078] Optionally, tantalum nitride (e.g., Ta 3 N5 ) have a charge imbalance and can have an oxygen to anion (O / N+O) molar ratio of 4.0% or more (e.g., a molar ratio of 5.0% to about 18%, or 6.0% to 18%, or 7.0% to 18%, or 8.0% to 18%, or 9.0% to 18%, or 10% to 18%, etc.).

[0079] Optionally, tantalum nitride (e.g., Ta 3 N 5 ) is Ta 3+ or Ta 4+ , or V N , or O N Alternatively, the tantalum nitride may be substantially free or detectably free of one or more of the reduced species such as. As used herein and throughout, "substantially free" (unless otherwise specified) may be less than 15 at%, less than 10 at%, less than 5 at%, less than 2.5 at%, less than 1.5 at%, less than 1 at%, less than 0.5 at%, less than 0.2 at%, less than 0.1 at%, less than 0.05 at%, less than 0.01 at%, or less than 0.001 at%. N represents a nitrogen vacancy, and V N , V N , V N ·, V NΦ And V N , V N , V N ·, and V NΦ are V with 0, 1, 2, and 3 trapped electrons, respectively. N V has an unpaired electron. N and V NΦ This indicates that only O may be EPR active. N is the oxygen impurity (e.g., O 2- )

[0080] The tantalum nitride of the present invention can act as a catalyst alone or can optionally be part of a catalyst. The tantalum nitride as a catalyst of the present invention can be used with one or more cocatalysts and / or can be modified and / or doped with one or more metals and / or can be impregnated or surface coated with one or more metals.

[0081] The catalyst of the present invention may be a photocatalyst, which is active in various light waves or regions, such as ultraviolet light and visible light (i.e., in the visible light region).

[0082] The promoter may be, for example, at least one CoO x The promoter may be at least one metal oxide such as the promoter alone, or may be a metal promoter, or both. The promoter may be platinum (Pt), or may include platinum (Pt), or may further include platinum (Pt). The promoter may be, include, or further include a metal such as, but not limited to, gold, platinum, cobalt, palladium, silver, nickel, or any combination thereof. The promoter may be Cr, 2 O 3 It may be, include, or further include:

[0083] The cocatalysts, such as metal cocatalysts (e.g., Pt), are either CoOx cocatalysts or Cr 2 O 3 It can be used in combination with another cocatalyst such as

[0084] The tantalum nitride of the present invention functions as a catalyst, such as a photocatalyst, to produce oxygen from decomposed water and can be used in combination with a second catalyst, such as a photocatalyst, capable of producing hydrogen from the decomposed water.

[0085] Therefore, optionally, the present invention may be a combination of two catalysts, a water oxidation catalyst and a water reduction catalyst. The two catalysts can be used together as a mixture. The two catalysts can be used in sequence, such as using a water reduction catalyst after a water oxidation catalyst, or using a water reduction catalyst after a water oxidation catalyst. The two catalysts can be used in such a way that they can be added separately for the water splitting reaction, but can be present together during the water splitting reaction.

[0086] When two catalysts are used, both catalysts can be used in equal amounts (weight ratio), or one catalyst can be used in greater amounts than the other. For example, the weight ratio of the water oxidation catalyst to the water reduction catalyst can be 10:1 to 1:10, such as 7.5:1 to 1:7.5, 5:1 to 1:5, 3:1 to 1:3, 2:1 to 1:2, 1.5:1 to 1:1.5, 1.2:1 to 1:1.2, 1.1:1 to 1:1.1, etc.

[0087] Alternatively, the tantalum nitride of the present invention can function as a dual catalyst, such as a dual photocatalyst, producing oxygen from the decomposition of water and also producing hydrogen from the decomposition of water. In this option, the tantalum nitride is modified in at least two ways so that it can achieve both catalytic functions. The tantalum nitride can be modified as described herein (e.g., Ta modified with at least one cocatalyst). 3 N 5 Nanoparticles, e.g., at least one metal oxide, e.g., CoO x Ta modified with promoter 3 N 5 nanoparticles), and modified or doped with one or two metals such as Zr and / or Mg (e.g., Ta 3 N 5 : Mg+Zr, or Ta 3 N 5 : Mg or Ta 3 N 5 :Zr, or a combination thereof). 2+ and / or Zr 4+ All cations are Ta 3 N 5In yet another modification, tantalum nitride is present in the crystal lattice of Ta 3 N 5 : Only Mg+Zr may be used. Tantalum nitride is Ta 3 N 5 : Mg alone or Ta 3 N 5 In each of these, Mg and / or Zr may be Ta. 3 N 5 It exists as a cation in the crystal lattice.

[0088] In terms of dual catalytic and water reduction functions, tantalum nitride is 3 N 5 : Mg+Zr, or Ta 3 N 5 : Mg or Ta 3 N 5 :Zr, or any combination thereof, the tantalum nitride can have Mg to cation (e.g., Mg / (Ta+Mg+Zr)) and Zr to cation (e.g., Zr / (Ta+Mg+Zr)) ratios as high as 9.0 mol% and 10.2 mol%, respectively. The Mg to cation ratio is 1-9 mol%, 2-9 mol%, 3-9 mol%, 4-9 mol%, 5-9 mol%, 6-9 mol%. The Zr to cation ratio is 1-10.2 mol%, 2-10 mol%, 3-10 mol%, 4-10 mol%, 5-10 mol%, 6-10 mol%, 7-10 mol%, or 8-10 mol%.

[0089] Tantalum nitride is used for its moisture reduction function. x :M1 or TaN x :M1+M2, or any combination thereof, where x ranges from 0.1 to 3, and M1 and M2 represent metal cations (e.g., Mg, Zr, Li, Sc, Ti, Hf, Al, or Ga), but M1 and M2 are not the same.

[0090] The tantalum nitride of the present invention functions as a catalyst by itself, such as a photocatalyst, and has the ability to split water without the aid of a co-catalyst.

[0091] The use of one or more cocatalysts or metals is preferred. When both functions, i.e., water oxidation and water reduction, are desired, metals such as Pt and, optionally, Cr are used. 2 O 3 or other metal oxides (e.g., Cr on Pt). 2 O 3 Uniform thin layer of Pt / Cr 2 O 3 (forming a core-shell nanostructure). The loading of the metal, such as Pt or other metal, can be at least 0.1 wt.%, at least 0.5 wt.%, or at least 0.9 wt.%, or at least 1 wt.%, based on the weight of the catalyst.

[0092] The tantalum nitride of the present invention can be used alone as a catalyst, such as a photocatalyst, and has the ability to split water without the use of a sacrificial reagent.

[0093] Optionally, the tantalum nitride of the present invention may function as a catalyst, either alone or with one or more co-catalysts, such as, for example, a photocatalyst as described herein, and is capable of splitting water and reacting with one or more sacrificial reagents (e.g., sacrificial electron donors), such as, but not limited to, AgNO 3 can be decomposed using

[0094] The tantalum nitride of the present invention can be used alone as a catalyst such as a photocatalyst, and has the ability to split water under ultraviolet light irradiation or visible light.

[0095] The co-catalyst may be distributed or dispersed on the nanoparticles, such as uniformly distributed or dispersed on the single crystal nanoparticles. Alternatively or additionally, the co-catalyst may be mixed with the nanoparticles or used in any manner in combination with the nanoparticles.

[0096] Preferably, the co-catalyst is uniformly distributed on the surface of the single crystal nanoparticles (e.g., the weight of the co-catalyst varies by ±10% anywhere on the surface). Optionally, there is no detectable agglomeration of the co-catalyst or no detectable agglomeration of the co-catalyst with the nanoparticles.

[0097] The present invention further relates to a method for producing the nanoparticles of the present invention.

[0098] Catalyst (e.g., Ta 3 N 5 The method of producing the nanoparticles may include or involve subjecting either spherical tantalum powder or salt-valve metal aggregates (e.g., tantalum aggregates with a salt aggregate such as NaCl) to a mild nitridation process. "Mild nitridation" refers to the process of nitriding tantalum powder by the addition of NH 3 or the like. The method can include performing the nitridation at an elevated temperature of 700K or higher or other temperature (e.g., 700K to 1300K, or 725K to 1175K, or 750K to 1175K, or 775K to 1300K, or 800K to 1300K, or 850K to 1300K, or 900K to 1300K, or 925K to 1175K, or 773K to 1223K) under a flow of gas such as nitridation gas. The method can be performed at a temperature of 700K to 1300K or 900K to 1150K for 10 minutes to 40 hours or more, or 1 hour to 8 hours, or 8 hours to 32 hours or more.

[0099] The method for producing tantalum nitride is to convert tantalum metal (Ta) into tantalum nitride (e.g., Ta 3 N 5 The tantalum may be a spherical tantalum powder (such as one having an aspect ratio of 1.4 to 1 or 1.2 to 1 as determined by measuring the diameter on the shortest diameter measurement and the longest diameter measurement of the particle) or may be flame-synthesized tantalum, which may optionally be encapsulated with a salt such as NaCl.

[0100] Conversion to tantalum nitride can be accomplished by a nitridation process, which involves nitriding tantalum nitride at elevated temperatures of 700 K or higher or other temperatures (e.g., 700 K to 1300 K, 725 K to 1175 K, 750 K to 1175 K, 775 K to 1300 K, 800 K to 1300 K, 850 K to 1300 K, 900 K to 1300 K, 925 K to 1175 K, or 773 K to 1223 K) with NH 3 The method includes, but is not limited to, nitriding tantalum under a gas flow such as ... x This can include impregnating the tantalum nitride with the promoter or a precursor thereof.

[0101] For the nitridation process, the gas in the gas stream is NH 3 The nitrogen-containing gas may be, for example, a nitrogen-containing gas such as 0.01 g or more, 0.1 g or more, 1.0 g or more, or 10.0 g or more. The flow rate of the gas may be 10 ml / min or more, 100 ml / min or more, 150 ml / min or more, or 200 ml / min or more, measured at room temperature (25° C.) and room temperature pressure (1 atmosphere). The amount of tantalum converted to tantalum nitride in the nitriding step may be 0.01 g or more, 0.1 g or more, 1.0 g or more, or 10.0 g or more.

[0102] The tantalum used is as follows: The method of manufacture is one in which the starting material is a tantalum manufacturing process that includes or is flame synthesis or sodium / halide flame encapsulation (SFE). Techniques used in SFE processes applicable to the manufacture of the starting tantalum powder of the present invention are described in U.S. Patents 5,498,446 and 7,442,227, which are incorporated herein by reference in their entirety. See also Barr, JL et al., "Processing salt-encapsulated tantalum nanoparticles for high purity, ultra high surface area applications," J.Nanoparticle Res. (2006), 8:11-22. An example of a chemical reaction used to manufacture metal powders by the SFE process of U.S. Patent 5,498,446 is as follows, where "M" refers to a metal such as Ta: MCl x +XNa+Inert → M+XNaCl+Inert. Tantalum pentachloride is reacted with MCl x is an example of a tantalum halide that can be used as a catalyst, and in this chemical reaction, argon gas may be used as an inert gas and carrier gas. First, particles (e.g., Ta) are produced in a flame and grow by solidification while the salt remains in the vapor phase. The salt condenses on and / or around the Ta particles with heat loss, and the uncoated core particles may be removed by the salt particles.

[0103] The tantalum used may be a powder such as that obtained by the SFE process without any salt encapsulation or coating.

[0104] The tantalum used may be a powder such as that obtained by the SFE process, and a powder containing a salt layer or encapsulation, such as NaCl / Ta powder.

[0105] At least one promoter, such as at least one metal oxide, such as CoO xImpregnation of tantalum nitride with a promoter or its precursor includes, but is not limited to, Co(NO 3 ) 2 6H 2 This can be achieved by using metal precursors such as co-precursors such as O. Other examples of metal precursors include Mn(NO 3 ) 2 ·(H 2 O) n , Fe(NO 3 ) 3 ·(H 2 O) n , Ni(NO 3 ) 2 ·(H 2 O) n , Ru(NO 3 ) 3 ·(H 2 O) n , CoCl 2 ·(H 2 O) n , MnCl 2 ·(H 2 O) n , FeCl 3 ·(H 2 O) n , NiCl 2 ·(H 2 O) n , IrCl 3 ·(H 2 O) n , and RuCl 3 ·(H 2 O) n Including, but not limited to:

[0106] The method of preparing catalysts using co-catalysts involves the co-catalyst loading of single crystal nanoparticles (e.g., CoO x and Pt loading). Each unique cocatalyst serves to catalyze the same or a different chemical reaction. For example, a single crystal nanoparticle can have a first cocatalyst loading useful for catalyzing the oxidation of water (production of oxygen) and a second cocatalyst loading useful for catalyzing the reduction of water (production of hydrogen).

[0107] Ta 3 N 5 CoO nanoparticles x The method of reforming with promoters can be achieved by impregnation, followed by NH 3 Generally, for example, Ta 3 N 5 The powder was prepared by adding Co(NO 3 ) 2 6H 2 The metal precursor, such as Co(NO), can be immersed in an aqueous solution containing the necessary or desired amount of metal precursor, such as Co(NO). This forms a slurry. This slurry is continuously stirred for a period of time (e.g., 1 to 5 minutes or more) using sonication (e.g., high intensity sonication) or other similar dispersing methods to disperse the metal precursor, such as Co(NO). 3 ) 2 In a metal precursor solution such as Ta 3 N 5 The powder is completely dispersed. The modified nanoparticles can then be recovered by any technique, such as drying in a hot water bath. The resulting powder mixture is then heated, for example, at a temperature of 500 K or higher, e.g., 773 K for 1 hour or other time, in a NH 3 Gas flow (100 mL min -1 or less or more) to obtain CoO x Modified Ta 3 N 5 Nanoparticle photocatalysts such as metal oxide Ta 3 N 5 A nanoparticle photocatalyst can be obtained.

[0108] The above method can be applied to other Co precursors and / or other metal precursors to modify tantalum nitride with this type of cocatalyst.

[0109] Supporting the cocatalyst may involve or include the deposition of one or more cocatalysts (e.g., Pt) by an impregnation reduction (IMP) method. This method involves the addition of tantalum nitride (previously supported with or without a first cocatalyst) to a cocatalyst-containing compound or cocatalyst precursor (e.g., a Pt-containing compound or H 2 PtCl 6The process involves dispersing the powder in water with a Pt precursor such as ZnO (Pt precursor) to form a slurry, which is then heated with hot water vapor such as steam until it becomes dry. The powder is then cooled to room temperature. 2 / N 2 Gas flow (H 2 :20mL / min, N 2 The catalyst is heated at 250° C. for 1 hour under a flow rate of 200 mL / min (flow ration: 200 mL / min) to obtain tantalum nitride carrying a promoter.

[0110] Co-catalyst loading (e.g., Pt loading) may involve or include deposition of the co-catalyst (e.g., Pt) by an in-situ photodeposition (PD) method. In this method, a co-catalyst precursor (e.g., Pt precursor) may be added to an aqueous solution containing tantalum nitride (pre-loaded with or without a first co-catalyst) nanoparticles. Under photocatalytic reaction conditions, the co-catalyst (e.g., Pt) may be loaded in-situ on the tantalum nitride nanoparticles.

[0111] The support of the co-catalyst (e.g., Pt support) can be carried out by a combination of IMP and PD methods. For example, the support of the co-catalyst (e.g., Pt support) can be carried out in a stepwise manner. The IMP-PD stepwise method includes the deposition of the co-catalyst (e.g., Pt) by IMP as a seed (first step) and the further seed growth of the co-catalyst (e.g., Pt) by in-situ PD (second step).

[0112] In the combination of the IMP and PD processes, the cocatalyst loading (e.g., Pt loading) by the photodeposition (PD) process can account for 70% to 95% of the total cocatalyst loading (e.g., Pt loading by Pt weight %) by cocatalyst weight %.

[0113] The catalysts of the present invention can be used in processes for splitting water or other fluids (e.g., aqueous fluids, where fluid refers to a liquid or gas) to produce, for example, hydrogen (in the form of hydrogen gas or hydrogen protons) and also oxygen (in the form of oxygen gas or oxygen molecules).

[0114] (CoOx The nanoparticles of the present invention (having metal oxides such as , , etc.) are particularly useful for the water splitting portion to produce oxygen and can be used in combination with catalysts that are particularly useful for the water splitting portion to produce hydrogen. Each catalyst (catalyst for producing oxygen and catalyst for producing hydrogen) can be used together or sequentially in any order. As shown above, the same catalyst can be a dual-purpose catalyst and can perform both functions of splitting water to produce oxygen and hydrogen.

[0115] More specifically, the present invention further includes a method for catalytically splitting water into the elements hydrogen and oxygen, comprising: 2 The oxidation reaction to produce 3 N 5 Nanoparticles, e.g. CoO x Ta modified with metal oxides as promoters 3 N 5 This includes the use of nanoparticles.

[0116] The method of catalytically splitting water into the elements hydrogen and oxygen is O 2 In addition to the oxidation reaction to produce H, H can be produced by utilizing any of the catalysts (i.e., water reduction catalysts) described in U.S. Provisional Patent Application No. 63 / 184816, filed May 6, 2021, or WO2022 / 235721, which are incorporated by reference herein. 2 The details and descriptions of the water reduction catalysts and methods of making and using the same described in U.S. Provisional Patent Application No. 63 / 184816 or WO2022 / 235721 can be employed herein to modify or include in the catalyst of the invention (either in the same catalyst or in combination with a water oxidation catalyst).

[0117] Thus, in accordance with the present invention, as part of the method of the present invention, 2The reduction reaction can further include a reduction reaction to produce Ta. The reduction reaction can optionally utilize single crystal nanoparticles that are tantalum nitride doped with at least one metal. 3 N 5 : Mg+Zr, Ta 3 N 5 :Mg, Ta 3 N 5 In the reduction reaction, single crystal nanoparticles of Ta, Zr, or any combination thereof can be used. 3 N 5 : Mg+Zr, Ta 3 N 5 :Mg, Ta 3 N 5 :Zr, or any combination thereof, can be utilized along with at least one co-catalyst (eg, Pt).

[0118] The aqueous fluid may be water. The aqueous fluid may be a water-based fluid. The aqueous fluid may be an alcohol.

[0119] In the methods of the present invention, the catalyst, such as a photocatalyst, may be a heterogeneous phase in contact with the fluid or solution.

[0120] The method can include applying energy to water or an aqueous fluid in the presence of a catalyst to split water molecules into hydrogen and oxygen.

[0121] The energy source may be solar energy. The energy source may be light energy. The energy source may be ultraviolet light. The energy source may be visible light. The energy source may be infrared (IR) energy. The energy source may be visible light radiation. The energy source may be at least 20 mW / cm 2 , or at least 40 mW / cm 2 , or at least 60 mW / cm 2 , or at least 80 mW / cm 2 , or at least 100 mW / cm 2 , or at least 200 mW / cm2 , or at least 300 mW / cm 2 , or at least 400 mW / cm 2 , or at least 500 mW / cm 2 , or at least 600 mW / cm 2 , or at least 700 mW / cm 2 , or at least 800 mW / cm 2 , or at least 900 mW / cm 2 , or at least 1000 mW / cm 2 It can provide irradiation of.

[0122] The catalyst may be suspended or present in water, an aqueous fluid, or other fluid.

[0123] The catalyst can be attached to a surface and can be in contact with water or an aqueous or other fluid.

[0124] The water or aqueous or other fluid may be moving or stationary relative to the catalyst.

[0125] The catalyst can be present in any amount. For example, if the catalyst is suspended in water or an aqueous or other fluid, the amount can be at least 0.15 g / 150 ml of fluid, or at least 0.2 g / 150 ml, or at least 0.5 g / 150 ml, or other amounts below or above any of these ranges. Similar amounts can be used when the catalyst is immobilized on a surface.

[0126] Although the invention and various embodiments are described herein, in the course of developing the invention, 3 N 5 It has been unexpectedly discovered that the specific parameters and materials used to form Ta can have a significant effect on the catalyst properties. 3 N 5 The catalyst is particularly preferred, especially when used as a photocatalyst.

[0127] In one preferred embodiment, the Ta material used is a spherical Ta metal powder, preferably with an average particle size of 25 nm to 100 nm, or about 50 nm to 100 nm. Best results have been obtained with an average spherical particle size of less than 100 nm. The nitridation of the spherical Ta powder has unexpectedly produced superior Ta nitridation when nitrided at a temperature of at least 1150K, or at least 1160K, or at least 1170K, e.g., 1150K to 1230K, or 1170K to 1230K. 3 N 5 The nitriding time is at least 1 hour, or at least 2 hours, or at least 3 hours, or at least 4 hours, which is optimal, and the best catalytic properties are obtained when the nitriding time is between 4 and 8 hours. x The amount of CoO was preferably 0.2% by weight to 0.8% by weight, for example 0.3% by weight to 0.7% by weight, or 0.35% by weight to 0.5% by weight, or about 0.5% by weight. x Above 0.5 wt. % loading, the catalytic activity actually decreased. Most preferred is 0.35 wt. % to 0.5 wt. %, or about 0.5 wt. %. These parameters provide excellent crystallinity and low defect density, light absorption, and photocatalytic activity. 2 generation (e.g., O under visible light irradiation) 2 A catalyst with high photocatalytic activity for the generation of fluorine has been provided.

[0128] In a further preferred embodiment, the Ta material used is a salt-mixed Ta metal nanopowder, such as NaCl-mixed Ta metal nanopowder (e.g., NaCl cubic crystals and Ta metal nanoparticles). The salt content, such as NaCl, can be in an amount of 10% to 75% by weight, for example, 25% to 60% by weight, or 35% to 60% by weight, or 40% to 60% by weight, or 50% to 60% by weight, or about 55% by weight (based on the total weight of Ta and salt). The presence of the salt during the nitriding process unexpectedly works well as a molten salt flux during the nitriding process, resulting in highly dispersed Ta. 3 N 5 The formation of nanoparticle single crystals was promoted. 3 N5 The crystals were monodisperse, rod-like crystals with smooth exposed facets. 3 N 5 The grain size of the crystals increases with the nitriding temperature. 3 N 5 It is possible to obtain single crystal Ta with clear lattice fringes without grain boundaries from the surface to the interior, and Ta was grown by using a salt (NaCl) mixed Ta metal precursor. 3 N 5 It is shown that nanoparticles were formed. The preferred nitridation process conditions are actually lower than those when using spherical Ta. Here, the preferred nitridation temperature is about 1000K to 1100K, for example, 1050K to 1100K, or about 1073K. The nitridation time that gives the best properties is 8 hours to 32 hours, more preferably about 10 hours to 24 hours, and most preferably 12 hours to 18 hours, or 14 hours to 17 hours, or about 16 hours. With such preferred conditions, the produced catalyst is photocatalytic O at the irradiated wavelength. 2 Developing Ta 3 N 5 Nanoparticle O 2 It showed the best photocatalytic performance in terms of generation and apparent quantum yield (AQY). Unexpectedly, the use of salts such as NaCl as flux resulted in well-defined Ta nanoparticles without grain boundaries or defect states. 3 N 5 It was found that single crystal nanoparticles could be obtained. x This Ta modified with a promoter 3 N 5 In nanoparticles, O 2 A fairly high photocatalytic activity for the generation of O was achieved. 2 The AQY of the generated GaN is high, at least 5%, e.g., 5% to 10%, e.g., 9.4% at 420 nm (± 25 nm). These parameters ensure excellent crystallinity and low defect density, light absorption, and photocatalytic O 2 generation (e.g., O under visible light irradiation) 2 A catalyst with high photocatalytic activity for the generation of fluorine has been provided.

[0129] Thus, the present invention provides, in part, a method for producing thermal NH3O4-based photocatalysts useful for forming photocatalysts for solar energy conversion. 3 It concerns the use of suitable starting materials for the production of active nanoscale single crystal nitrides by nitridation.

[0130] The present invention is further defined by the following examples, which are intended as purely exemplary of the invention. EXAMPLES

[0131] Material Procurement

[0132] Ta 3 N 5 Flame synthesised (SFE) Ta powder in the form of NaCl-free Ta metal nanopowder (w / oNaCl / Ta) for synthesis (also called Ta nanopowder precursor) and NaCl mixed Ta metal nanopowder (NaCl / Ta) (NaCl:Ta=55:45 wt%) were supplied by Global Advanced Metals USA, Inc. 2 Co(NO 3 ) 2 6H 2 O (99.95%), AgNO as a sacrificial electron donor 3 (99.9%), and the buffer La 2 O 3 (99.9%) were purchased from Kanto Chemical Co., Ltd., Fujifilm Wako Pure Chemical Industries, Ltd., and Kojundo Chemical Laboratory Co., Ltd., respectively.

[0133] Ta 3 N 5 Synthesis of nanoparticles

[0134] In this embodiment, Ta 3 N 5 Nanoparticles were produced by nitridation of Ta metal nanopowder (w / oNaCl / Ta) or NaCl-mixed Ta metal nanopowder (NaCl / Ta). 0.4–0.5 g of Ta metal nanopowder (w / oNaCl / Ta) or 0.6–0.7 g of NaCl-mixed Ta metal nanopowder (NaCl / Ta) were transferred into an alumina tube and nitrided with NH at 100 mL / min.3 Nitridation was carried out under gas flow at various temperatures and time ranges (measured at room temperature and atmospheric pressure). NaCl mixed Ta metal nanopowder precursor was ground in an agate mortar for 5 min before nitridation. The nitrided samples were washed in ultrapure water at 343 K for 2 h and then dried completely at room temperature overnight.

[0135] Chief of Staff x Promoted by Ta 3 N 5 Nanoparticle Modification

[0136] In this embodiment, CoO x Promoted by Ta 3 N 5 The modification of nanoparticle photocatalysts was carried out by impregnation followed by NH 3 This was done by heat treatment under flow. 3 N 5 The powder was prepared by adding the required amount of Co(NO 3 ) 2 6H 2 The slurry was continuously stirred with powerful sonication for 5 min and the Ta 3 N 5 The powder was dissolved in Co(NO 3 ) 2 The slurry was dried in a hot water bath, and the resulting powder mixture was then dissolved in NH 3 Heating at 773 K for 1 h under a gas flow (100 mL / min) yielded CoO x Modified Ta 3 N 5 Nanoparticle photocatalysts were obtained. Unless otherwise stated, in all examples, CoO x The promoter was added up to 0.5% by weight of the catalyst.

[0137] Material characterization

[0138] Where stated, the following analytical techniques were used. X-ray diffraction (XRD) patterns were obtained using a Rigaku MiniFlex 300 powder diffractometer with Cu Kα radiation operated at 30 kV and 30 mA. UV-vis diffuse reflectance spectra (DRS) were recorded using a spectrophotometer (V-670, JASCO) equipped with an integrating sphere, and a Spectralon standard was used as a reference for baseline correction. Scanning electron microscopy (SEM) images were acquired on a Hitachi SU8020 system and a JEOL JSM-7600F. High-resolution transmission electron microscopy (HRTEM) was performed using a JEOL JEM-2800 system and a JEM-2100F system.

[0139] Photocatalyst O 2 Reaction

[0140] Photocatalyst O 2 The evolution reaction was carried out in a Pyrex top-lit reaction vessel connected to a closed gas circulation system. 0.15 g CoO x Modified Ta 3 N 5 0.15 g La as photocatalyst and pH buffer 2 O 3 150 mL of AgNO 3 The reaction mixture was dispersed in an aqueous solution (0.2 M). The temperature was maintained at 285 K by circulating cooling water. After the reaction slurry was completely evacuated to remove all air, the suspension was irradiated with a 300 W xenon lamp equipped with a cold mirror and a cut-off filter (L42, λ ≥ 420 nm). During the reaction, the reaction solution was maintained at 288 K by a cooling water system. The evolved gas products were analyzed using an integrated thermal conductivity detector-gas chromatography system (TCD-GC) consisting of a GC-8A chromatograph (Shimadzu) equipped with a molecular sieve 5A column with argon as the carrier gas. The sensitivity of the TCD was calibrated by analyzing a known amount of gas introduced into a fully evacuated reaction system containing the reaction solution under irradiation. The deposition of Ag particles on the photocatalyst resulted in the formation of O 2 The rate of generation is often reduced, so photocatalytic O 2The evolution activity was estimated from the initial gas evolution rate.

[0141] Apparent quantum yield measurements

[0142] O 2 Under the evolution reaction conditions, the apparent quantum yield (AQY) of the photocatalytic reaction is expressed as AQY(%)=[4×R] / I×100, where R and I represent the gas evolution rate and the incident photon flux, respectively. The factor 4 is the sacrificial AgNO 3 Photocatalyst O from 2 Four electrons are involved in the reaction to produce one molecule of O 2 The light source was, for example, a 300W Xe lamp (MAX-303 Compact Xenon Light Source, Asahi Spectra) equipped with bandpass filters (center wavelengths 380, 400, 420, 440, 500, 560, and 600 nm (full width at half maximum = 15 nm), respectively). The number of incident photons was measured using a LS-100 grating spectroradiometer (EKO Instruments Co., Ltd.).

[0143] Example 1

[0144] Ta from Ta metal nanopowder 3 N 5 Photocatalysis on nanoparticles 2 occurrence.

[0145] As mentioned above, Ta 3 N 5 Generally, NH is used as the nitrogen source. 3 Tantalum oxide (Ta) is formed at high temperatures in the presence of gas. 2 O 5 In this reaction, Ta 5+ In order to maintain the high oxidation state of Ta, three oxygen atoms must be replaced by two nitrogen atoms. 3 N 5 The formation of 3A slow diffusion process of solid anions in the atmosphere is required, which results in the reduction of Ta species and the generation of a certain amount of oxygen impurities. To avoid this problem, in the present embodiment, spherical Ta metal nanopowder (w / oNaCl / Ta) with an average particle size of about 50-100 nm was used as the precursor (Figure 5). The Ta metal precursor (w / oNaCl / Ta) was nitrided to produce Ta 3 N 5 Forming the Ta phase is a completely different reaction process due to the change in the chemical state of Ta. Figure 1 shows the XRD patterns of the Ta nanoparticle precursor (w / oNaCl / Ta) and the intermediate phase of Ta nanopowder nitrided at 773 K to 1173 K. The Ta nanoparticle precursor (w / oNaCl / Ta) formed a metallic phase (Ta 0 ) was.

[0146] The nitriding temperature is generally set to the final Ta 3 N 5 The Ta nanopowder precursor (w / oNaCl / Ta) is a promising candidate for the Ta-based nanopowder because it plays an important role in determining the crystallinity and defect density of the product. 3 N 5 Nanoparticle crystallinity, optical absorption, and photocatalysis 2 The effect of different nitridation temperatures on the evolution of Ta was investigated. As shown in Figure 2A, the XRD patterns of the nitridation samples prepared at 1123K–1223K for 4 h were significantly different from the standard Ta 3 N 5 This is in good agreement with the pattern (Fig. 11C) of pure Ta in this temperature range. 3 N 5 As the nitridation temperature increases, the intensity of the diffraction peaks changes slightly and gradually increases, which means that the crystallinity of the samples treated at higher temperatures (1173K or 1223K) is better than that of the sample treated at 1123K. According to UV-VisDRS (Figure 2B), the absorption edge of these samples is located around 600 nm, which is close to the Ta 3 N 5 However, the background absorption of the sample increases with increasing temperature, suggesting that more defects are formed with increasing nitridation temperature.

[0147] Both the crystallinity and defect level are Ta 3 N 5 The nitridation temperature affects the photocatalytic performance of Ta, with higher crystallinity (higher photocatalytic performance) and higher defect levels (lower photocatalytic performance). 3 N 5 CoO x Modification with cocatalyst and photocatalytic O 2 The generation of Ta was measured at 1173K. 3 N 5 The nanoparticles were then subjected to O 2 It was found that the photocatalytic activity against the generation of Ta was the highest (Fig. 2C). 3 N 5 showed similar crystallinity to that treated at 1173K, but the background absorption results in Figure 2B show that it had more defects and was slightly less active than that treated at 1173K.

[0148] In addition to the nitridation temperature, the nitridation period is also important for the photocatalytic activity. The Ta nanopowder precursor (w / oNaCl / Ta) was nitrified at 1173 K for 1 to 8 h to obtain Ta 3 N 5 followed by the formation of CoO x Modification with cocatalyst and photocatalytic O 2 Figure 7A shows the CoO x Ta modified with promoter 3 N 5 From Ta 3 N 5 and O 2 The XRD patterns of the generation activity are shown, where Ta 3 N 5 was produced by nitriding at 1173K for 1 to 8 hours. Ta nitrided for 4 hours 3 N 5 The nanoparticles are similar to other Ta 3 N 5The diffraction intensity was slightly stronger than that of the Ta nanopowder sample, and the photocatalytic performance was higher. 3 N 5 The optimal synthesis conditions for the growth of single crystal nanoparticles were determined.

[0149] O 2 Considering that the generation promoter provides active catalytic sites on the photocatalyst surface and improves charge transfer, Ta was synthesized at 1173 K for 4 h. 3 N 5 Using nanoparticles, CoO x The effect of the amount of cocatalyst on photocatalytic performance was investigated (Figure 8). Ta nanopowder precursor (w / oNaCl / Ta) was synthesized at 1173 K for 4 h. 3 N 5 CoO nanoparticles x Modified with cocatalyst. CoO x Co(NO) as a Co precursor in the cocatalyst reforming procedure 3 ) 2 6H 2 By adjusting the amount of O, 0.2 wt%, 0.35 wt%, 0.5 wt%, and 0.7 wt% CoO x A cocatalyst-supported material was produced. O 2 The occurrence was measured. x The activity increased with the loading of CoO x An optimum level is reached at a content of 0.5 wt%, after which CoO x It was observed that as the content was further increased the activity decreased.

[0150] Ta nitrided at 1173K for 4 hours 3 N 5 Detailed morphological information of the nanoparticles was observed by SEM and HRTEM. As shown in Figure 2D and Figure 2E, Ta 3 N 5 The samples exhibit irregular crystalline shapes with small grain sizes less than 100 nm. Small crystal size is advantageous for photocatalytic performance because it shortens the travel distance of electrons and holes to the surface of the photocatalyst and greatly reduces the chance of charge recombination. The enlarged images of the red and blue boxed areas in Figure 2E (indicated by the arrows in Figure 2E) show that Ta3 N 5 Clear diffraction fringes and clear grain boundaries were observed inside the nanoparticles. 3 N 5 It is confirmed that the nanoparticles are sufficiently crystallized as single crystals, although some agglomerations occur.

[0151] Example 2

[0152] Ta from NaCl mixed Ta metal nanopowder (NaCl / Ta) 3 N 5 Photocatalysis on nanoparticles 2 The generation was originally composed of NaCl cubic crystals and Ta metal nanoparticles (Figure 9). NaCl-mixed Ta metal nanopowder was dissolved in NH 3 When nitrided for 16 hours at 1023K, 1073K, 1123K, and 1173K under air flow, the pure Ta 3 N 5 phase is obtained, and as the temperature increases, the Ta 3 N 5 The crystallinity of Ta nanopowder was increased (Fig. 3A). Fig. 3C shows the Ta nanopowder produced from NaCl mixed with Ta metal nanopowder (NaCl / Ta). 3 N 5 The SEM image of the nanoparticles is shown. The 55 wt% NaCl in the mixture acts as a molten salt flux during the nitridation process, forming highly dispersed Ta 3 N 5 The formation of nanoparticle single crystals was promoted by the action of NaCl flux. 3 N 5 The nanoparticles were monodisperse rod-shaped crystals with smooth exposed surfaces. 3 N 5 The grain size of the crystals increases with the nitriding temperature, which is in good agreement with the increase in intensity of the XRD pattern (Figure 3A). 3 N 5 HRTEM images of the nanoparticles show clear lattice fringes from the surface to the interior without grain boundaries, and single-crystalline Ta was synthesized using a NaCl mixed Ta metal precursor (NaCl / Ta). 3 N 5 This shows that nanoparticles were formed (Figure 3D).

[0153] Ta produced from NaCl mixed Ta metal nanopowder (NaCl / Ta) 3 N 5 Single crystal CoO nanoparticles x Modification with cocatalyst, photocatalyst O 2 The generation of highly dispersed Ta was measured using NaCl mixed Ta metal nanopowder (NaCl / Ta). 3 N 5 The nanoparticle single crystals were prepared by the Ta metal precursor (w / oNaCl / Ta). 3 N 5 AgNO as a hole sacrificial reagent compared to nanoparticles (Figure 2C). 3 Using O 2 The photocatalytic performance for the generation of Ta was improved (Fig. 3B). 3 N 5 Nanoparticle photocatalysis 2 Developmental activity was the highest among the samples at various other temperatures (Fig. 3B).

[0154] In addition to the nitridation temperature, the nitridation period was also found to be important for the photocatalytic activity. NaCl mixed Ta metal nanopowder (NaCl / Ta) was nitrified at 1073 K for 8 to 32 h to obtain Ta 3 N 5 followed by the formation of CoO x Modification with cocatalyst and photocatalytic O 2 The generation of Ta was measured (Fig. 10A-C). When the nitriding time was extended from 8 hours to 16 hours, 3 N 5 Both the crystallinity and particle size of the nanoparticles increased, and the photocatalytic 2 The occurrence of Ta was improved by increasing the nitriding time. 3 N 5 Particle O 2 The generation activity gradually decreased, which is believed to be due to the increased charge transfer distance and reduced surface area within the larger particles.

[0155] Monodispersed single crystal Ta synthesized from NaCl mixed Ta nanopowder (NaCl / Ta) at 1073K for 16 hours 3N 5 Nanoparticles are 2 The photocatalyst showed the best photocatalytic performance against the generation of ozone. 2 Developing Ta 3 N 5 The dependence of the apparent quantum yield (AQY) of nanoparticles on the irradiation wavelength is shown in Figure 4. The AQY increases at wavelengths below 400 nm, peaks at 400 nm, and then gradually decreases to a minimum between 420 nm and 600 nm, whereas the AQY of Ta nanopowder prepared from NaCl mixed with Ta nanopowder (NaCl / Ta) is significantly higher than that of Ta nanopowder prepared from NaCl mixed with Ta nanopowder (NaCl / Ta). 3 N 5 The absorption profile of the nanoparticles was in good agreement with that of the Ta nanoparticles. The AQY values ​​were 9.4% at 420 nm (± 25 nm) and 5.4% at 500 nm (± 25 nm), which is consistent with that of the Ta nanoparticles simply prepared from the precursor without surface or bulk modification. 3 N 5 The photocatalytic efficiency is relatively high. This is because the metallic Ta nanopowder has no defect states or grain boundaries and is an efficient photocatalytic material. 2 High quality Ta that leads to development 3 N 5 This shows that it is a promising material for producing nanoparticle photocatalysts.

[0156] In summary, as shown in the examples, NH 3 Through the oxidation process in nitridation, single crystal Ta 3 N 5 Nanoparticles were produced from Ta metal to Ta 3 N 5 The rapid transformation to the Ta phase allows high-quality Ta to be obtained under relatively mild nitriding conditions. 3 N 5 Moreover, the use of NaCl as a flux enabled the formation of clearly defined Ta nanoparticles without grain boundaries or defect states. 3 N 5 Single crystal nanoparticles were obtained. x This Ta modified with a promoter 3 N 5 In nanoparticles, O 2 A fairly high photocatalytic activity for the generation of O was achieved. 2The AQY of the generated NH was as high as 9.4% at 420 nm (± 25 nm). The results of this study indicate that the thermal NH 3 The effectiveness of using suitable starting materials for the production of active nanoscale single crystal nitrides by nitridation was confirmed.

[0157] The present invention includes the following aspects / embodiments / features in any order and / or in any combination: 1. The present invention relates to a method for x Single crystal Ta modified with promoter 3 N 5 nanoparticles, wherein the MO x is a metal oxide, M is a metal, and O x represents an oxide that is a part of a metal oxide. 2. MO x is the CoO x A cocatalyst, x represents an oxide that is a part of cobalt oxide, 3 N 5 Nanoparticles or methods or other embodiments. 3. MO x The cocatalyst is a single crystal of Ta. 3 N 5 Ta in an amount of at least 0.01 wt. % based on the total weight of the nanoparticles 3 N 5 The monocrystalline Ta of any one of the preceding or following embodiments / features / aspects, which is impregnated into nanoparticles. 3 N 5 Nanoparticles or methods or other embodiments. 4. MO x The cocatalyst is a single crystal of Ta. 3 N 5 Ta in an amount of at least 0.5 wt. % based on the total weight of the nanoparticles 3 N 5 The monocrystalline Ta of any one of the preceding or following embodiments / features / aspects, which is impregnated into nanoparticles. 3 N 5 Nanoparticles or methods or other embodiments. 5. MO x The promoter is CoO, Co 2 O, Co 2 O 3 , and / or Co. 3 O 4 The single crystal Ta according to any one of the preceding or following embodiments / features / aspects, 3 N 5 Nanoparticles or methods or other embodiments. 6. Single crystal nanoparticles contain more than 0.1% photocatalytic O 2 The monocrystalline Ta of any one of the above or below embodiments / features / aspects having an apparent quantum yield of the emission reaction (OER). 3 N 5 Nanoparticles or methods or other embodiments. 7. Single crystal nanoparticles are photocatalytic with 0.1% to 9.4% O 2 A single crystal Ta of any one of the preceding or following embodiments / features / aspects having an apparent quantum yield of the emission reaction (OER). 3 N 5 Nanoparticles or methods or other embodiments. 8. The single-crystal Ta nanoparticles of any of the preceding or following embodiments / features / aspects, wherein the single-crystal nanoparticles are also doped with at least one metal. 3 N 5 Nanoparticles or methods or other embodiments. 9. A single crystal nanoparticle or single crystal Ta according to any of the preceding or following embodiments / features / aspects, in which platinum and / or other metal catalysts are dispersed on the surface of the single crystal nanoparticle. 3 N 5 A catalyst comprising nanoparticles (or a method of using same). 10. A single crystal nanoparticle or single crystal Ta according to any preceding or following embodiment / feature / aspect having a sunlight-to-hydrogen (STH) energy conversion efficiency of greater than 0.015%. 3 N 5 A photocatalyst comprising nanoparticles (or a method for using the same). 11. A photocatalyst or single crystal Ta according to any one of the preceding or following embodiments / features / aspects, having a sunlight-to-hydrogen (STH) energy conversion efficiency of 0.015% to 0.1%. 3 N 5 Nanoparticles or methods or other embodiments. 12. A method comprising the steps of: (a) administering to a patient a single crystal nanoparticle of any of the preceding or following embodiments / features / aspects; and (b) administering to a patient a single crystal nanoparticle of any of the preceding or following embodiments / features / aspects; and (c) administering to a patient a single crystal nanoparticle of any of the preceding or following embodiments / features / aspects; and (d) administering to a patient a single crystal nanoparticle of any of the preceding or 2 The photocatalyst or single crystal Ta according to any of the preceding or following embodiments / features / aspects, 3 N 5 Nanoparticles or methods or other embodiments. 13. H 2 The photocatalyst or single crystal Ta according to any one of the above or following embodiments / features / aspects has a production rate of 5 μmol / h to 13 μmol / h. 3 N 5 Nanoparticles or methods or other embodiments. 14. The photocatalyst or single crystal Ta according to any of the preceding or following embodiments / features / aspects, having an apparent quantum yield (AQY) of greater than 0.15%. 3 N 5 Nanoparticles or methods or other embodiments. 15. The photocatalyst or single crystal Ta according to any one of the above or below embodiments / features / aspects, wherein the AQY is 0.15% to 0.54%. 3 N 5 Nanoparticles or methods or other embodiments. 16. Furthermore, H 2 The photocatalyst or single crystal Ta according to any of the preceding or following embodiments / features / aspects, having a production rate of more than 5 μmol / h or an apparent quantum yield (AQY) of more than 0.15%, or both. 3 N 5 Nanoparticles or methods or other embodiments. 17. A single crystal Ta according to any of the preceding or following embodiments / features / aspects. 3 N 5 Photocatalysts (or methods of using same) comprising nanoparticles or other embodiments. 18. The photocatalyst or single crystal Ta according to any of the preceding or following embodiments / features / aspects, carried out in a fluid or solution with an energy source. 3 N 5 A method for splitting water comprising utilizing nanoparticles. 19. O 2 The photocatalyst or single crystal Ta according to any of the preceding or following embodiments / features / aspects, wherein the oxidation reaction to produce Ta is carried out in a fluid or solution together with an energy source. 3 N 5 A method for catalytically splitting water into hydrogen and oxygen, comprising utilizing nanoparticles. 20. H 2 The method (or catalyst or nanoparticle) of any preceding or following embodiment / feature / aspect, further comprising a reduction reaction to produce 21. The method (or catalyst or nanoparticles) of any preceding or following embodiment / feature / aspect, wherein the reduction reaction uses single-crystalline nanoparticles of tantalum nitride doped with at least one metal. 22. In a reduction reaction, Ta 3 N 5 : Mg+Zr, Ta 3 N 5 :Mg, Ta 3 N 5 The method (or catalyst or nanoparticle) according to any preceding or following embodiment / feature / aspect, wherein single-crystalline nanoparticles are used which are Zr, Mn, Fe, or any combination thereof. 23. In a reduction reaction, Ta 3 N 5 : Mg+Zr, Ta 3 N 5 :Mg, Ta 3 N 5 The method (or catalyst or nanoparticles) according to any preceding or following embodiment / feature / aspect, wherein single-crystalline nanoparticles, which are Zr, Fe, or any combination thereof, and at least one co-catalyst are used. 24. A method for producing single crystal nanoparticles of any preceding or following embodiment / feature / aspect, said method comprising subjecting either spherical tantalum powder or tantalum agglomerates with salt agglomerates, or flame-synthesized tantalum, which may optionally be encapsulated with salt, to a nitridation process, said nitridation process comprising subjecting NH 3 The tantalum nitride was formed by nitriding the tantalum nitride under flow at a temperature of 700 K or higher for 10 minutes to 32 hours. The tantalum nitride was then nitrided by MO x This involves impregnation with a promoter. 25. The method (or catalyst or nanoparticle) of any preceding or following embodiment / feature / aspect, wherein the temperature is from 700K to 1200K for from 1 hour to 8 hours. 26. The method comprises adding MgCl to tantalum nitride. 2 or other first metal salts and ZrOCl 2 The method (or catalyst or nanoparticle) of any preceding or following embodiment / feature / aspect, further comprising impregnating the nanoparticle with a salt of, or another second metal. 27. The single-crystal Ta nanoparticles of any preceding or following embodiment / feature / aspect, wherein the single-crystal Ta nanoparticles are monodisperse nanorod particles. 3 N 5 Nanoparticles or methods or other embodiments. 28. The monocrystalline Ta of any preceding or following embodiment / feature / aspect, wherein the monodisperse nanorod particles have an average length of 50 nm to 500 nm. 3 N 5 Nanoparticles or methods or other embodiments. 29. The method (or catalyst or nanoparticle) of any preceding or following embodiment / feature / aspect, wherein the photocatalyst is a heterogeneous phase in contact with a fluid or solution. 30. The monocrystalline Ta according to any preceding or following embodiment / feature / aspect, wherein the energy source is solar energy. 3 N 5 Nanoparticles or methods or other embodiments. 31. Single crystal nanoparticles can be irradiated with at least 200 μmol / h of O 2The single crystal Ta according to any preceding or following embodiment / feature / aspect, 3 N 5 Nanoparticles or methods or other embodiments. 32. Single crystal nanoparticles can be irradiated with at least 300 μmol / h of O 2 The single crystal Ta according to any preceding or following embodiment / feature / aspect, 3 N 5 Nanoparticles or methods or other embodiments. 33. Single crystal nanoparticles can deliver at least 450 μmol / h of O 2 The single crystal Ta according to any preceding or following embodiment / feature / aspect, 3 N 5 Nanoparticles or methods or other embodiments. 34. The method includes subjecting spherical tantalum powder having an average particle size of 20 nm to 100 nm to a nitriding process at a temperature of 1150 K to 1230 K for 4 to 8 hours, and preparing MO with a loading of 0.3 wt % to 0.7 wt % of tantalum nitride. x The monocrystalline Ta according to any preceding or following embodiment / feature / aspect, which comprises impregnating a co-catalyst. 3 N 5 Nanoparticles or methods or other embodiments. 35. A single crystal Ta according to any of the preceding or following embodiments / features / aspects. 3 N 5 In the nanoparticles or method or other embodiments, the method includes subjecting the tantalum aggregates with the salt aggregates, or the salt encapsulated flame synthesized tantalum, to a nitridation process at a temperature of 1000K to 1100K for 8 hours to 32 hours, and nitriding the tantalum nitride with a loading of 0.3 wt % to 0.7 wt % MO. x This involves impregnating the promoter. 36. The single crystal tantalum of any preceding or following embodiment / feature / aspect, wherein the tantalum aggregate with the salt aggregate or the salt-encapsulated flame-synthesized tantalum has a salt content of 25% to 70% by weight based on the weight of the tantalum and salt. 3 N 5Nanoparticles or methods or other embodiments. 37. The impregnation is performed by using the Ta 3 N 5 The nanoparticles are mixed with a metal precursor, such as a Co precursor, to form a dispersed slurry, followed by recovery and drying of the recovered modified nanoparticles, and then NH 3 By heating the material to temperatures above 500 K under a gas flow, MO x Ta modified with promoter 3 N 5 The method (or catalyst or nanoparticles) according to any preceding or following embodiment / feature / aspect, comprising obtaining nanoparticles. 38. A MO produced from the method (or catalyst or nanoparticle) according to any preceding or following embodiment / feature / aspect. x Ta modified with promoter 3 N 5 Nanoparticles. 39. The single-crystal Ta nanoparticle according to any preceding or following embodiment / feature / aspect, wherein the single-crystal Ta nanoparticle is also doped with at least two metals. 3 N 5 Nanoparticles or methods or other embodiments. 40. The single-crystal Ta nanoparticles according to any preceding or following embodiment / feature / aspect, wherein the single-crystal nanoparticles are also co-doped with two metals. 3 N 5 Nanoparticles or methods or other embodiments. 41. Single crystal nanoparticles were also doped with Ta. 3 N 5 : Mg+Zr, Ta 3 N 5 :Mg, Ta 3 N 5 :Zr, or any combination thereof, according to any preceding or following embodiment / feature / aspect. 3 N 5 Nanoparticles or methods or other embodiments. 42. a)MO x Single crystal Ta modified with promoter 3 N 5 Nanoparticles (where O xrepresents an oxide that is a part of cobalt oxide), and 2) a catalyst containing modified or doped Zr and / or Mg. 43. A method for catalytically splitting water into elemental hydrogen and oxygen, the method comprising the step of: 3 N 5 The present invention includes utilizing nanoparticles or methods or other embodiments.

[0158] The present invention may include any combination of the various features or embodiments described above and / or below in sentences and / or paragraphs. Any combination of features disclosed herein is considered to be part of the present invention, and no limitations are intended with respect to features that may be combined.

[0159] It should be understood that the disclosure herein refers to specific illustrated examples, which are presented by way of example and not by way of limitation. The foregoing detailed description discusses exemplary embodiments, but is intended to be construed to cover all modifications, alternatives, and equivalents of those embodiments that may fall within the spirit and scope of the invention as defined by the additional disclosure.

[0160] The entire contents of all references cited in this disclosure are incorporated herein by reference, to the extent they do not contradict this disclosure.

[0161] The present invention may include any combination of the various features or embodiments described above and / or in the following claims, sentences and / or paragraphs. Any combination of features disclosed herein is considered part of the present invention, and no limitations are intended with respect to features that may be combined.

[0162] Other embodiments of the invention will be apparent to those skilled in the art from consideration of the specification and practice of the invention disclosed herein. It is intended that the specification and examples be considered only in light of the following claims, with a true scope and spirit of the invention being indicated by the following claims and equivalents thereof.

[0163] Drawing Terminology Intensity 2θ / degree 2θ / degree KM Function (arb. unit) Wavelength / nmWavelength / nm Rate of O 2 evolution / μmol h -1 O 2 Generation rate / μmol h -1 Nitridation temperature BLUE Blue RED Amount of O2 evolved / μmol O 2 Generated amount / μmol Irradiation time / h Chief of Staff x loading content CoO x Loading Content

Claims

1. M.O. x Single crystal Ta modified with promoter 3 N 5 Nanoparticles, wherein M is a metal and O x represents an oxide that is a part of a metal oxide. 3 N 5 Nanoparticles.

2. M.O. x is CoO x A cocatalyst comprising O x represents an oxide that is a part of the cobalt oxide, 3 N 5 Nanoparticles.

3. M.O. x The co-catalyst is single crystal Ta. 3 N 5 Ta in an amount of at least 0.01 wt. % based on the total weight of the nanoparticles. 3 N 5 The single crystal Ta of claim 1, which is impregnated into nanoparticles. 3 N 5 Nanoparticles.

4. M.O. x The co-catalyst is single crystal Ta. 3 N 5 Ta in an amount of at least 0.5 wt. % based on the total weight of the nanoparticles 3 N 5 The single crystal Ta of claim 1, which is impregnated into nanoparticles. 3 N 5 Nanoparticles.

5. M.O. x The promoter is CoO, Co 2 O.C.O. 2 O 3 and / or Co 3 O 4 The single crystal Ta according to claim 1, 3 N 5 Nanoparticles.

6. Single crystal nanoparticles contain more than 0.1% photocatalytic O 2 The single crystal Ta of claim 1, which has an apparent quantum yield of the evolution reaction (OER). 3 N 5 Nanoparticles.

7. The single crystal nanoparticles contain 0.1% to 9.4% photocatalytic O 2 The single crystal Ta of claim 1 has an apparent quantum yield of the evolution reaction (OER). 3 N 5 Nanoparticles.

8. The single crystal nanoparticles of claim 1 are doped with at least one metal. 3 N 5 Nanoparticles.

9. The single crystal Ta according to claim 1 3 N 5 A catalyst comprising nanoparticles and a platinum and / or other metal catalyst dispersed on the surface of the single crystal nanoparticles.

10. The single crystal Ta according to claim 1 3 N 5 A photocatalyst comprising nanoparticles and having a sunlight-to-hydrogen (STH) energy conversion efficiency of greater than 0.015%.

11. The photocatalyst of claim 10, having a sunlight-to-hydrogen (STH) energy conversion efficiency of 0.015% to 0.1%.

12. The single crystal Ta according to claim 1 3 N 5 Nanoparticles and more than 5 μmol / h H 2 A photocatalyst having a production amount.

13. The H 2 The photocatalyst according to claim 12, wherein the production rate is from 5 μmol / h to 13 μmol / h.

14. The single crystal Ta according to claim 1 3 N 5 A photocatalyst comprising nanoparticles and having an apparent quantum yield (AQY) of greater than 0.15%.

15. The photocatalyst according to claim 14, wherein the AQY is 0.15% to 0.54%.

16. Furthermore, H 2 11. The photocatalyst of claim 10, having a production rate of more than 5 μmol / h or an apparent quantum yield (AQY) of more than 0.15%, or both.

17. The single crystal Ta according to claim 1 3 N 5 Photocatalysts containing nanoparticles.

18. 20. A method for splitting water comprising utilizing the photocatalyst of claim 17 in a fluid or solution together with an energy source.

19. A method for catalytically splitting water into the elements hydrogen and oxygen, comprising the steps of: 2 The method of claim 17, wherein the oxidation reaction to produce

20. H 2 20. The method of claim 19, further comprising a reduction reaction to produce:

21. 21. The method of claim 20, wherein the reduction reaction uses single crystal nanoparticles of tantalum nitride doped with at least one metal.

22. In the reduction reaction, Ta 3 N 5 : Mg + Zr, Ta 3 N 5 :Mg, Ta 3 N 5 21. The method of claim 20, wherein single crystal nanoparticles are used that are Zr, Fe, or any combination thereof.

23. In the reduction reaction, Ta 3 N 5 : Mg + Zr, Ta 3 N 5 :Mg, Ta 3 N 5 21. The method of claim 20, wherein single crystal nanoparticles of Zr, Fe, Cu, FeN, Cu ...

24. The single crystal Ta according to claim 1 3 N 5 A method for producing nanoparticles, the method comprising subjecting either spherical tantalum powder or tantalum agglomerates with salt agglomerates, or flame-synthesized tantalum, which may optionally be encapsulated with a salt, to a nitridation process, the nitridation process comprising subjecting NH 3 The tantalum nitride is then formed by nitriding the tantalum nitride under a flow at a temperature of 700K or higher for 10 minutes to 32 hours. x impregnating with a promoter.

25. 25. The method of claim 24, wherein the temperature is from 700K to 1200K for a period of from 1 hour to 8 hours.

26. The method includes the step of: 2 or other first metal salt and ZrOCl 2 or other second metal salt.

27. The single crystal nanoparticles of claim 1 are monodisperse nanorod particles. 3 N 5 Nanoparticles.

28. The monodisperse nanorod particles have an average length of 50 nm to 500 nm. 3 N 5 Nanoparticles.

29. 20. The method of claim 18, wherein the photocatalyst is a heterogeneous phase in contact with a fluid or solution.

30. 30. The method of claim 29, wherein the energy source is solar energy.

31. Single-crystal nanoparticles have a molecular weight of at least 200 μmol h -1 O 2 The single crystal Ta of claim 1 provides a high generation rate. 3 N 5 Nanoparticles.

32. Single-crystal nanoparticles have a molecular weight of at least 300 μmol h -1 O 2 The single crystal Ta of claim 1 provides a high generation rate. 3 N 5 Nanoparticles.

33. Single-crystal nanoparticles have a melting point of at least 450 μmol h -1 O 2 The single crystal Ta of claim 1 provides a high generation rate. 3 N 5 Nanoparticles.

34. The method comprises subjecting spherical tantalum powder having an average particle size of 20 nm to 100 nm to a nitriding process at a temperature of 1150 K to 1230 K for 4 to 8 hours to obtain tantalum nitride with a loading of 0.3 wt % to 0.7 wt % MO. x 25. The method of claim 24, comprising impregnating the promoter.

35. The method includes subjecting the tantalum aggregates with the salt aggregates or the salt encapsulated flame synthesized tantalum to a nitridation process at a temperature of 1000K to 1100K for 8 hours to 32 hours, and nitriding the tantalum nitride with MO at a loading of 0.3 wt % to 0.7 wt %. x 25. The method of claim 24, comprising impregnating the promoter.

36. 36. The method of claim 35, wherein the tantalum aggregate with salt aggregate or the salt encapsulated flame synthesized tantalum has a salt content of 25% to 70% by weight based on the weight of tantalum and salt.

37. The impregnation is performed by using the Ta 3 N 5 The nanoparticles are mixed with a metal precursor to form a dispersed slurry, followed by recovery and drying of the recovered modified nanoparticles, and then the nanoparticles are treated with NH 3 By heating at a temperature of 500 K or higher under a gas flow, MO x Ta modified with promoter 3 N 5 A method according to any one of claims 34 to 36, comprising obtaining nanoparticles.

38. MO produced by the method according to any one of claims 24 or 34 to 37. x Ta modified with promoter 3 N 5 Nanoparticles.

39. The single crystal nanoparticles of claim 1 are doped with at least two metals. 3 N 5 Nanoparticles.

40. The single crystal Ta nanoparticles of claim 1 are co-doped with two metals. 3 N 5 Nanoparticles.

41. Single crystal nanoparticles were also doped with Ta. 3 N 5 : Mg + Zr, Ta 3 N 5 :Mg, Ta 3 N 5 10. The single crystal Ta of claim 1, wherein Zr, Ta+Zn, or any combination thereof is formed. 3 N 5 Nanoparticles.

42. a) MO x Single crystal Ta modified with promoter 3 N 5 Nanoparticles (wherein O x represents an oxide that is a part of cobalt oxide), and 2) a catalyst containing modified or doped Zr and / or Mg.

43. 43. A method for catalytically splitting water into elemental hydrogen and oxygen, said method comprising utilizing the catalyst of claim 42.

Citation Information

Patent Citations

  • US10,744,495

  • Photo-catalytic systems for the production of hydrogen

    US20140174905A1